Source and central level recovery of nutrients from urine and wastewater: A state-of-art on nutrients mapping and potential technological solutions. Issue 2 (April 2022) - Kundu, Sazal; Pramanik, Biplob Kumar; Halder, Pobitra; Patel, Savankumar; Ramezani, Mohammad; Khairul, M.A.; Marzbali, Mojtaba Hedayati; Paz-Ferreiro, Jorge; Crosher, Susan; Short, Graeme; Surapaneni, Aravind; Bergmann, David; et al.
Abstract: Wastewater treatment facilities typically transform nitrogen compounds into innocuous nitrogen. Phosphorous is partially recovered in biosolids while the potassium cycle in the treatment process is still not well mapped. This paper provides a mapping of the nutrients from household sources (urine, faeces and greywater) to wastewater in the traditional wastewater treatment plants. Following this mapping, the article critically reviews the nutrients recovery technologies, including their applicability at source (for urine) and centralised (for wastewater) levels, benchmarking, social acceptance, and techno-commercial assessments. Additionally, the paper has identified the current technological challenges and opportunities as well as suggested a several future recommendations for developing commercially viable nutrient recovery technologies from urine at source level and wastewater at wastewater treatment plants (centralised level). The high energy requirement, high cost and safety issues are some of the common challenges for most of the nutrient recovery technologies. However, anaerobic membrane bioreactor integrated with biochar or zeolite (for wastewater) and biosorption (for both urine and wastewater) can be highly attractive from those perspectives. Graphical Abstract: ga1 Highlights: The fate of N, P and K from urine, faeces and greywater to wastewater was comprehensively mapped. Nutrient recovery technologies were critically reviewed for both source and central level suitability. Social acceptance of urine-based fertiliser and economic feasibility analysis were presented. Technologies were benchmarked in terms of technological, economical, environmental and social aspects. Biosorption can be a sustainable route for nutrient recovery.